What makes IM users (un)responsive: An empirical investigation for understanding IM responsiveness. Issue 172 (April 2023) - Lee, Hao-Ping (Hank); Chiang, Yi-Shyuan; Chou, Yu-Ling; Lin, Kung-Pai; Chang, Yung-Ju
Abstract: Instant messaging (IM) communication has been widely studied due to its prevalence in our everyday communication. Numerous factors that contribute to (un)responsiveness have been identified. Yet an integrated view of the factors that influence IM responsiveness remains absent. This paper reports qualitative findings from interviews with 46 IM users, and identifies five main elements underlying IM users' response decisions: response habits, need fulfillment, perceived obligation, perceived readiness/suitability, and pace/rhythm coordination . To the best of our knowledge, this is the first integrated view of the key elements underlying IM responsiveness. Among these elements, we particularly highlight that regarding the influence of contextual factors on IM responsiveness, what may matters more is IM users' perceptions of their readiness and suitability of the contexts, rather than the contexts' objective properties. We also uncovered pace/rhythm coordination as a crucial factor behind IM responsiveness, which has been little discussed in the literature. Responsiveness, as our findings show, was often not a consequence, but a manifestation, of users' pursuit of specific responsiveness-related aims such as ongoing shaping and sustaining of a dyad's pace and rhythm. Highlights: IM responsiveness is linked to habit, need, obligation, perception, and coordination. The impact of contextual factors on IM responsiveness is subjective and perceptual. IM responsiveness often manifests as an intention to shape a communicative pattern.